Postoperative Pulmonary Dysfunction and Mechanical Ventilation in Cardiac Surgery - Rafael Badenes; Angels Lozano; F. Javier Belda (Critical Care Research and Practice)
Postoperative pulmonary dysfunction (PPD) is a frequent and significant complication after cardiac surgery. It contributes to morbidity and mortality and increases hospitalization stay and its associated costs. Its pathogenesis is not clear but it seems to be related to the development of a systemic inflammatory response with a subsequent pulmonary inflammation. Many factors have been described to contribute to this inflammatory response, including surgical procedure with sternotomy incision, effects of general anesthesia, topical cooling, and extracorporeal circulation (ECC) and mechanical ventilation (VM). Protective ventilation strategies can reduce the incidence of atelectasis (which still remains one of the principal causes of PDD) and pulmonary infections in surgical patients. In this way, the open lung approach (OLA), a protective ventilation strategy, has demonstrated attenuating the inflammatory response and improving gas exchange parameters and postoperative pulmonary functions with a better residual functional capacity (FRC) when compared with a conventional ventilatory strategy. Additionally, maintaining low frequency ventilation during ECC was shown to decrease the incidence of PDD after cardiac surgery, preserving lung function.